Management and Marketing of Genetically Improved Carp: Slides presented at training workshops - Hamilton, Matthew; Yeasin, Mohammed; Reza Hossain, Mostafa Ali (WorldFish, 2023)
This manual includes slides presented at two workshops conducted in Bangladesh in October 2022. Topics addressed in these workshops were the WorldFish Carp Genetic Improvement Program (CGIP), genetic theory, broodfish genetics and broodfish care.